Radiopaque lesions in orofacial soft tissue. Clinical and epidemiological behavior and therapeutic management in indwelling patients - Orlando Guerra Cobian; Leonor Liudmila Fuentes Puebla; Sonia Felipe Torres (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: The radiopacities in the orofacial soft tissue appears habitually as an incidental finding in panoramic x-rays, exhibiting a relatively low frequency. Objective: To identify the frequency of orofacial radiopaque lesions in soft tissue in indwelling patients, its clinical consequences and therapeutic management. Material and Methods: A descriptive transversal study was carried out in the Dentistry Faculty "Raúl Gómez García", from January 2014 to January 2016. The sample was constituted by 578 patients evaluated by the multidisciplinary Implantology service, who had a panoramic study with properly established inclusion criteria. To each patient was performed an interrogatory, clinical exam and exhaustive analysis of his panoramic x-ray. The analyzed variables included: age, sex, denomination, presence of pathological previous entities, presence of clinical findings at the moment of examination, and therapeutic management. Results: The radiopaque lesions appeared in 4,7% of the sample analyzed, they prevailed in males (3,1%), the idiopathic calcifications reported a 66,6% and the sialoliths a 55,5%. A 66,6%  of discoveries were asymptomatic. A 33,4% needed removal  of radiopacities with associate tissue. Conclusions: The radiopaque lesions  of orofacial soft tissue in indwelling patients are not very frequent, the idiopathic calcifications  prevails,  particularly the sialoliths, and most of the lesions require therapeutic handling. Keywords: Radiopaque lesions, soft tissue, orofacial, frequency, therapeutic handling, patients, indwelling.